Lolo Jose an intimate portrait of Rizal - Bantug, Asuncion Lopez (Pasig City EC Graphics, 1999)
Contains the full text of the novel in a virtual reality environment. It also contains the lineage of Jose Rizal, his works as an artist and scientist, and photographs of his life. The author also included some notes on the chapters of the novel and trivia items relating to the novel. A video introduction is presented prior to the viewing of the actual novel.
Bong Villegas, narrator; Ed Malata, music
Keywords: Rizal, Jose P. -- 1861-1896.; Bantug, Asuncion Lopez